If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 5) = -5(2x + -3) + x Reorder the terms: 5(5 + x) = -5(2x + -3) + x (5 * 5 + x * 5) = -5(2x + -3) + x (25 + 5x) = -5(2x + -3) + x Reorder the terms: 25 + 5x = -5(-3 + 2x) + x 25 + 5x = (-3 * -5 + 2x * -5) + x 25 + 5x = (15 + -10x) + x Combine like terms: -10x + x = -9x 25 + 5x = 15 + -9x Solving 25 + 5x = 15 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 25 + 5x + 9x = 15 + -9x + 9x Combine like terms: 5x + 9x = 14x 25 + 14x = 15 + -9x + 9x Combine like terms: -9x + 9x = 0 25 + 14x = 15 + 0 25 + 14x = 15 Add '-25' to each side of the equation. 25 + -25 + 14x = 15 + -25 Combine like terms: 25 + -25 = 0 0 + 14x = 15 + -25 14x = 15 + -25 Combine like terms: 15 + -25 = -10 14x = -10 Divide each side by '14'. x = -0.7142857143 Simplifying x = -0.7142857143
| 23+6y-15=62 | | 5y=x+19 | | 189s=99+10 | | 7x-18=9x+4 | | 5(y-2)=-5y+40 | | 10x=4y+16 | | -c^2-5c+66= | | 3u+37=-5(u+9) | | 10x+x-4x= | | 5x-3-x=14-3x+11 | | 2k+8-4k=28 | | -18x^2+6x+24=0 | | Z^6=1 | | 23+14s=65 | | 23s+14=65 | | 3y^2-2x^2+2xy-6=0 | | 14x+3x+7x= | | 3.2=1.35h | | 2(j-20)+3=10 | | 3*1+y=9 | | 3*4+y=9 | | y-9=-11-y | | 4p-24=27-13p | | m-56=101 | | 3y+7=2y+7 | | 2y-5x=-60 | | w^2-9w+2=0 | | 4xsquared+3x+2x= | | o=364-120 | | (8x-4)-(9n-1)=12 | | C^2=0 | | 6(X+2)=2x+10 |